Bayesian reliability models of weibull systems: state of the art - Zaidi, Abdelaziz; Ould Bouamama, Belkacem; Tagina, Moncef (Zielona Góra: Uniwersytet Zielonogórski)
In the reliability modeling field, we sometimes encounter systems with uncertain structures, and the use of fault trees and reliability diagrams is not possible. To overcome this problem, Bayesian approaches offer a considerable efficiency in this context. This paper introduces recent contributions in the field of reliability modeling with the Bayesian network approach. Bayesian reliability models are applied to systems with Weibull distribution of failure.
Keywords: hierarchical modeling; reliability; Weibull; Bayesian networks; fault diagnosis